Acceleratory and inhibitory effects of uniaxial tensile stress on the photo-oxidation of polyethylene: Dependence of stress, time duration and temperature. (18th July 2018) - Liu, Qiang; Yang, Heng; Zhao, Jincan; Liu, Shixiang; Xia, Lei; Hu, Ping; Lv, Yadong; Huang, Yajiang; Kong, Miqiu; Li, Guangxian
Abstract: The photo-oxidation behavior of high density polyethylene (HDPE) subjected to uniaxial tensile stress is investigated at various temperatures, tensile stress levels and time durations. The effect of stress on the photo-oxidation rate of HDPE is found to be non-monotonous. Tensile stress is found to play distinctly different roles, namely showing acceleratory or inhibitory effect, with the elapse of aging time and at different temperatures. Stress-induced aging inhibition is prone to occur at low temperatures and high stresses within an appropriate aging duration. With elevating temperature, however, this inhibition effect disappears gradually and the stress is found to accelerate the aging process. Microstructural analysis reveals that the effect of stress is closely related to the interplay between the changes in the surface morphology as well as amorphous aggregation structure of materials and the photochemical degradation during aging, which is induced by the variation of molecular orientation and packing state in amorphous region, stress transfer efficiency, thermodynamic and kinetic aspects of photochemical reaction process. Graphical abstract: Taking stress level, time duration and aging temperature into consideration, the acceleratory and inhibitory effects of uniaxial tensile stress on the photo-oxidation of HDPE is investigated. Based on this study, we try to clarify the origin of the intricate and contradictory experimental phenomena that stress shows diverse roles in the degradation of polymer materials. The interplay between the changes in the surface morphology as well as amorphous aggregation structure and the photochemical degradation process during aging is responsible for these phenomena. More exactly, the so-called interplay includes the variation of molecular orientation and packing state in amorphous region, stress transfer efficiency, thermodynamic and kinetic aspects of photochemical reaction process. Image 1 Highlights: Effect of tensile stress level, temperature and time duration are considered for the photo-oxidation of HDPE. The stress displays acceleratory or inhibitory effect on the photo-oxidation. Molecular orientation, stress transfer efficiency, thermodynamic/kinetic aspects of photochemical reaction are discussed. A schematic diagram is constructed to reveal the role of stress by analogy to the TTS method.